Attenuation of immobilization stress-induced hypertension by temperature-controllable warm needle acupuncture in rats and the peripheral neural mechanisms - Bang, Se Kyun; Chang, Suchan; Seo, Su Yeon; Kang, Suk-Yun; Cho, Seong Jin; Choi, Kwang-Ho; Juping, Xing; Kim, Hee Young; Ryu, Yeonhee (Frontiers in Neurology, 2023)
We and others have shown that electrical stimulation of the PC-6 acupoint over the wrist relieves hypertension by stimulating afferent sensory nerve fibers and activating the central endogenous opioid system. Warm needle acupuncture has long been utilized to treat various diseases in clinics. Here, we developed a temperature-controllable warm needle acupuncture instrument (WAI) and investigated the peripheral mechanism underlying the effect of warm needle acupuncture at PC-6 on hypertension in a rat model of immobilization stress-induced hypertension. Stimulation with our newly developed WAI and traditional warm needle acupuncture attenuated hypertension development. Such effects were reproduced by capsaicin (a TRPV1 agonist) injection into PC-6 or WAI stimulation at 48°C. In contrast, PC-6 pretreatment with the TRPV1 antagonist capsazepine blocked the antihypertensive effect of WAI stimulation at PC-6. WAI stimulation at PC-6 increased the number of dorsal root ganglia double-stained with TRPV1 and CGRP. QX-314 and capsaicin perineural injection into the median nerve for chemical ablation of small afferent nerve fibers (C-fibers) prevented the antihypertensive effect of WAI stimulation at PC-6. Additionally, PC-6 pretreatment with RTX ablated the antihypertensive effect of WAI stimulation. These findings suggest that warm needle acupuncture at PC-6 activates C-fiber of median nerve and the peripheral TRPV1 receptors to attenuate the development of immobilization stress-induced hypertension in rats.